Fundamentals of galaxy dynamics, formation and evolution - Ferreras, Ignacio (UCL Press, 2019)
Ignacio Ferreras presents a concise introduction to extragalactic astrophysics, with emphasis on stellar dynamics, and the growth of density fluctuations in an expanding Universe. Additional chapters are devoted to smaller systems (stellar clusters) and larger ones (galaxy clusters).